Universal characterization of three-dimensional creeping crack-front stress fields. (November 2018) - Guo, Wanlin; Chen, Zhiyuan; She, Chongmin
Abstract: Creeping fracture in engineering always occurs in high temperature structures with complicated geometries and loading configurations, and how to characterize the three-dimensional crack border stress fields is essentially important to design of the structures. By comprehensive finite element analyses of specimens with through-the-thickness cracks and specimens with corner, surface and embedded elliptic cracks, we demonstrated that a three-parameter characterization based on C ( t ) integral, the out-of-plane stress constraint factor Tz and in-plane constraint coefficient Q * can be efficiently applied in all cases. It is shown that a two-parameter C ( t )– Tz solution can provide efficient prediction for the stress field ahead of the crack under small scale creep condition. Under large scale creep conditions, it is found that Tz has nearly a unified distribution ahead of cracks, and the three-parameter C ( t )– Tz –Q * solution can characterize the crack front stress fields efficiently. This universal characterization of the creeping crack front stress field should serve as a solid fundamental for three-dimensional damage tolerant design of high-temperature structures.